Pengaruh Kepercayaan dan Kualitas Pelayanan terhadap Kepuasan Pasien - Arnika Putri, Ni Putu Ayu Surya (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
This research was conducted with the aim of knowing the effect of Trust and Service Quality on Outpatient Patient Satisfaction at Karya Prima Clinic in Denpasar. The population in this study were Karya Prima Clinic patients in 2022 as many as 1907 people with a total sample of 95 respondents. Data analysis techniques used in this study were validity, reliability, classical assumptions, multiple linear regression, coefficient of determination, t test and F test. Based on the results of the study it can be seen that trust and service quality have a positive and significant effect partially and simultaneously on satisfaction outpatient. The magnitude of the influence of independent variables on patient satisfaction is 57.4%. Seeing the results of the research, the Karya Prima Clinic in Denpasar in the future must provide a suggestion box at the reception so that later the patient can provide suggestions and input to the hospital if there are deficiencies that the patient feels while undergoing treatment at the Karya Prima Clinic in Denpasar.